KEARIFAN LOKAL PANTAI LAUT SELATAN (MITOS NYI RORO KIDUL) SEBAGAI DESA WISATA DAN ASSET KABUPATEN SUKABUMI - Rahayu, Yuri (Sekolah Tinggi Pariwisata AMPTA, 2016)
Hearing the southern sea coast people will immediately think queenly figure, namely the southern coast guard Nyi Roro Kidul although the story will kebenerannya is still in question. Local knowledge is maintained continuity able to sustain life would be a tourist attraction and can increase the assets of government and society around. Local knowledge is a form of human effort in order to maintain, manage and preserve the indigenous culture and using his intellect (cognition) to act and behave towards something, objects or events that occur in a given space and dimension criteria to qualify as local wisdom. Qualitative research method is the right choice for this research because it aims to understand a phenomenon in the social context naturally. By having the natural attractions that are unique and distinctive and myths Nyi Roro Kidul attached, Pelabuhan Ratu eligible criteria of the tourist village and has the potential to bring assets and contribute in generating economical resources which are expected to provide benefits for the future and survival of the government and surrounding communities. Keywords: Asset, myth nyi Roro Kidul, tourist villages, local wisdom.